Drivers of Green Supply Chain Management (GSCM) among Halal Food Small Medium Enterprises (SMEs) / Aiman Naeim Mustaza - Mustaza, Aiman Naeim (Faculty of Business and Management, 2015)
In order to achieve Malaysia’s goal of becoming a Halal hub, one main area that we must emphasize is regarding environmental sustainability. As we are busy producing and promoting our Halal industry to the world, we must ensure the preservation of our environment. This is to make sure that our ventures continue to prosper and the environment is sustainable for our future generation. Due to the concern of sustaining the environment, many companies, worldwide have taken measures to preserve the environment. One of the popular method these days is the implementation of green supply chain management. Green supply chain management may contribute to the sustainability of the environment through waste reduction and the use of a less hazardous material or ‘green’ material along the supply chain process. However, in the scope of this country, very few have realized the benefits that green supply chain management has to offer. There are several main drivers that influence the implementation of green supply chain management. Therefore, the objective of this study is to study the relationship between the drivers; government rules and regulations, cost reduction, customer awareness and global climate pressure towards the implementation of green supply chain management among Halal food small medium enterprises in Seremban. This study was also conducted to indicate the main driver of GSCM. A set of questionnaire was developed by adapting questions from other past studies and also self-generated by the researcher from the literature review. The questionnaire was then distributed among Halal food small medium enterprises in Seremban. Data gathered were generated in the Statistical Package for Social Science (SPSS) and findings were analyzed. The research objectives and questions were then answered. This study was then concluded and several recommendations were provided for the purpose of future research in this particular topic.